A Room with Two Views: An Insight into the 1985 and 2007 Film Adaptations of E. M. Forster’s Novel - Elena Raicu (Cahiers Victoriens et Edouardiens)
Considered to be one of the best English-language novels of the last century, A Room with a View by E. M. Forster (1908) is firstly a Bildungsroman, being centered on the discovery made by a young woman –Lucy Honeychurch– of the world, of herself and of romance, and secondly, a critical portrayal of the English society. The novel was adapted for the screen twice: in 1985, based on a script by Ruth Prawer Jhabvala, and again in 2007, with the help of screenwriter Andrew Davies. The first film adaptation follows closely the original storyline, but Davies chooses to tell the same story from the main character’s point of view, as she recollects the past in a post-WWI period. While the innovation is welcome, in terms of form, it also changes in an unfortunate way Lucy’s life after the events of the novel and goes on a path which is different from Forster’s in A View without a Room (1958). Although this new ending might be the first noticeable difference between the two adaptations, they actually represent two quite distinct views of one story. The 1985 film adaptation meticulously illustrates the English society of the beginning of the 20th century and does justice to the Italian atmosphere used as a background in the first part of the story. Then, while clearly having Lucy Honeychurch as its main character, it delineates with great care the other characters as well. Their actions are justified by their thoughts, and all of these are defined by their personalities. This is not the case with the second adaptation, which focuses mainly on the heroine and emphasizes her sexual awareness. The other characters lack substance and are not always convincing in their roles, but are present only insofar as they come in contact with the heroine. The Italian and English societies are also pushed far in the background of the story. This is a one character-story. Therefore, if we are to consider that a film adaptation presents the story as seen through the lenses of the society contemporary with the filmmaking, we can justly ask ourselves what these two adaptations of A Room with a View tell us about the last part of the 20th century and about the first years of the 21st century.